Very Late Onset Schizophrenia Like Psychosis: A Case Report - Victoria, Vini; Bessing, Yulia Fatima; Yulianti, Erikavitri; Salma Nur Fadhilah (Jurnal Psikiatri Surabaya, 2025)
Introduction: With the growth of the aging population, we need to ensure that elderly people can live the rest of their lives with a satisfactory quality of life. However, the occurrence of psychosis in the elderly, especially at a later age, is a risk for decreased quality of life and a high risk of morbidity and mortality. The first episode of psychosis in age 60 or over is called very late-onset schizophrenia-like psychosis (VLOSLP) and needs to be distinguished from secondary psychosis such as Alzheimer’s Disease (AD) with psychotic symptoms. Case: A 77-year-old woman was brought by her family to the geriatric psychiatry clinic due to strange behavior such as hearing voices and obeying the voices’ commands since the last 6 months that worsened in the last month. In the last month, the patient also had sleeping difficulty, pacing at night, and accusing family of trying to harm her. After one month of therapy with Risperidone, the patient was showing improvement in the reduction of the voices. Discussion: The patient was assessed as VLOSLP with the first episode of psychosis with schizophrenia spectrum core symptoms such as paranoid delusion and auditory-verbal hallucination.  Conclusion: In this case, clinicians work with insufficient additional examination data, and that could also apply to clinicians in the remote area with no access to more comprehensive modalities to differentiate early stages of AD with psychosis and VLOSLP from clinical symptoms. However, more data is needed to establish clinical criteria regarding VLOSLP.